2006
DOI: 10.2337/diabetes.55.01.06.db05-0831
|View full text |Cite
|
Sign up to set email alerts
|

The Thromboxane Receptor Antagonist S18886 Attenuates Renal Oxidant Stress and Proteinuria in Diabetic Apolipoprotein E-Deficient Mice

Abstract: Arachidonic acid metabolites, some of which may activate thromboxane A 2 receptors (TPr) and contribute to the development of diabetes complications, including nephropathy, are elevated in diabetes. This study determined the effect of blocking TPr with S18886 or inhibiting cyclooxygenase with aspirin on oxidative stress and the early stages of nephropathy in streptozotocin-induced diabetic apolipoprotein E ؊/؊ mice. Diabetic mice were treated with S18886 (5 mg ⅐ kg ؊1 ⅐ day ؊1 ) or aspirin (30 mg ⅐ kg ؊1 ⅐ day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 47 publications
6
55
0
3
Order By: Relevance
“…These data may have important implications in clinical settings. TP activation is thought to contribute to the development of diabetic (types 1 and 2) complications (14,45,46), and diabetic mice have elevated PTEN levels (32,47). In a diabetic state, increased PTEN levels impair insulin signaling, acting to hamper EC responses to insulin, inhibit NO release, and increase the risk of smooth muscle cell hypertrophy and neointima formation.…”
Section: Discussionmentioning
confidence: 99%
“…These data may have important implications in clinical settings. TP activation is thought to contribute to the development of diabetic (types 1 and 2) complications (14,45,46), and diabetic mice have elevated PTEN levels (32,47). In a diabetic state, increased PTEN levels impair insulin signaling, acting to hamper EC responses to insulin, inhibit NO release, and increase the risk of smooth muscle cell hypertrophy and neointima formation.…”
Section: Discussionmentioning
confidence: 99%
“…S18886 (terubtroban) has been demonstrated to improve endothelial function in patients with coronary artery disease [64] and is currently compared with other antithombotic agents in a clinical trial (Prevention of cerebrovascular and cardiovascular Events of ischemic origin with teRutroban in patients with a history oF ischaemic strOke or tRansient ischemic attack PERFORM). In addition, a recent study showed a role of S18886 to reduce oxidative stress and expression of 12/15-LO [65].…”
Section: Thromboxane Receptor Amentioning
confidence: 98%
“…* Surface de lésions plus importante chez la souris ApoE-KO diabétique que chez la souris ApoE-KO normoglycémi-que (p < 0,05). ** Surface de lésions moins importante chez la souris ApoE-KO diabétique traitée avec le S18886 que chez la souris ApoE-KO diabétique non traitée (p < 0,05) (d'après [37]). ET PARTENARIAT RECHERCHE paramètres métaboliques (Figure 6) [31].…”
Section: Rôle Des Récepteurs Tp Dans L'athéroscléroseunclassified
“…Les récepteurs TP endothéliaux, contrairement aux récepteurs TP des plaquettes ou des cellules musculaires lisses, n'ont pas encore été étudiés en détail et leurs mécanismes doivent être éclaircis. Une première étude de Cohen et de ses collaborateurs indique que l'activation des récepteurs TP endothéliaux est impliquée dans les phénomènes d'oxydation présents dans la néphropathie diabé-tique [37]. Il semble évident que les antagonistes des récep-teurs TP, en inhibant les récepteurs TP endothéliaux, possèdent des propriétés anti-athéromateuses puissantes, comme l'a montré la recherche menée avec le terutroban.…”
Section: Rôle Des Récepteurs Tp Dans L'athéroscléroseunclassified
See 1 more Smart Citation